World Health Assembly 73: A Step Forward for Global Surgery - Gabrielle L. Cahill; Makela C. Stankey; Craig D. McClain; Kee B. Park (Ubiquity Press, 2021)
Member States at this year's World Health Assembly 73 (WHA73), held virtually for the first time due to the COVID-19 pandemic, passed multiple resolutions that must be considered when framing efforts to strengthen surgical systems. Surgery has been a relatively neglected field in the global health landscape due to its nature as a crosscutting treatment rather than focusing on a specific disease or demographic. However, in recent years, access to essential and emergency surgical, obstetric, and anesthesia care has gained increasing recognition as a vital aspect of global health. The WHA73 Resolutions concern specific conditions, as has been characteristic of global health practice, yet proper care for each highlighted disease is inextricably linked to surgical care. Global surgery advocates must recognize how surgical system strengthening aligns with these strategic priorities in order to ensure that surgical care continues to be integrated into efforts to decrease global health disparities.